Secular and Islamic feminist critiques in the work of Fatima Mernissi - Rhouni, Raja. (Women and Gender: The Middle East and the Islamic World, 2010)
This book presents a detailed critical analysis of the work of Fatima Mernissi. Mernissi is considered to be one of the major figures in Feminist thought for both Morocco and Muslim society in general. This work discusses Mernissi's intellectual trajectory from 'secular' to 'Islamic' feminism in order to trace the evolution of so-called Islamic feminist theory. The book also engages critically with the work of other Muslim feminists, using frameworks and approaches developed in the works of Muslim reformist thinkers, namely Mohammad Arkoun and Nasr Abu Zaid, with the aim of engaging the theorization of this emerging feminism.